TRIPLE HELIX MODEL, NOVEL STATE EDUCATIONAL STANDARDS AND EDUCATIONAL PROGRAMS AT THE UNIVERSITIES OF RUSSIA - Valery P. Shestak (Moscow Polytechnic University, 2017)
The Triple Helix model is that the potential for innovation and economic development in a Knowledge Society lies in a more prominent role for the university and in the hybridization of elements from university, industry and government to generate new institutional and social formats for the production, transfer and application of knowledge. This vision encompasses not only the creative destruction that appears as a natural innovation dynamics (Schumpeter, 1942), but also the creative renewal that arises within each of the three institutional spheres of university, industry and government, as well as at their intersections. The problem of interaction of the state, business and scientific community is actualized on the basis of recognition the system lagging of social and economic development of Russia from the other countries. This is confirmed by very modest positions taken by Russia in various international ratings. The possible solution of this problem in a format of «a social triangle of action » is offered: public-private partnership in case of implementation of investment projects, use of «Triple Helix» model in case of implementation of innovative projects and staffing based on professional educational standards of the new generation.